Adaptation Strategies Of Non-Muslim Msmes To Halal Certification Regulations In Manado City: The Perspective Of Maqasid Al-Syari’ah - Muhammad Sukri; Lomba Sultan; Muammar Muh. Bakry; Abdul Wahid Haddade (PT. Gudang Pustaka Cendekia, 2025)
This study discusses the adaptation strategies of non-Muslim MSMEs to halal certification regulations in Manado City from the perspective of Maqasid al-Syari'ah. This is a qualitative study. The research design is field research. The informants in this study consisted of MUI officials in North Sulawesi Province and non-Muslim MSME actors in Manado City. The results of this study indicate that: Non-Muslim SME actors have demonstrated a high level of adaptation to halal certification regulations through gradual and pragmatic strategies. They began by improving hygiene, recording raw materials, and participating in training and capacity-building programs. These strategies reflect that the actors do not reject the regulations but require an approach tailored to their capacities. In many cases, halal certification is even positioned as a branding tool and a means of market expansion, rather than merely legal compliance. This adaptation also reflects the success of a values-based approach rooted in the principles of maqasid, where regulations are accepted as meaningful and beneficial ethical business practices. Through a dialogic and contextual approach, non-Muslim SME operators have successfully transformed halal certification into an opportunity rather than a threat to their identity.